2016
DOI: 10.1038/srep37515
|View full text |Cite
|
Sign up to set email alerts
|

Multiple crosstalk between TOR and the cell integrity MAPK signaling pathway in fission yeast

Abstract: In eukaryotic cells, the highly conserved Target of Rapamycin (TOR) and the Mitogen Activated Protein Kinase (MAPK) signaling pathways elicit adaptive responses to extra- and intracellular conditions by regulating essential cellular functions. However, the nature of the functional relationships between both pathways is not fully understood. In the fission yeast Schizosaccharomyces pombe the cell integrity MAPK pathway (CIP) regulates morphogenesis, cell wall structure and ionic homeostasis. We show that the Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 55 publications
(110 reference statements)
1
30
0
2
Order By: Relevance
“…Our results support recently findings related to a cross‐regulatory relationship between CaMK and TOR pathways . And, significantly reduced transcription of the ght5 gene by increased iron stress has been thought that Ght5 protein might play a central role in complicated cross‐regulatory relationship.…”
Section: Discussionsupporting
confidence: 92%
“…Our results support recently findings related to a cross‐regulatory relationship between CaMK and TOR pathways . And, significantly reduced transcription of the ght5 gene by increased iron stress has been thought that Ght5 protein might play a central role in complicated cross‐regulatory relationship.…”
Section: Discussionsupporting
confidence: 92%
“…Whereas the reduction of the TORC1 activity leads to ectopic entry into sexual differentiation, the disruption of the psk1 gene shows little effect on the growth mode [ 20 ]. It has been recently suggested that Psk1 cooperates with TORC2-target Gad8 to adapt to cell integrity stress and glucose starvation, although the precise mechanism remains unclear [ 25 ].…”
Section: Conserved Phosphorylation Targets Of Torc1mentioning
confidence: 99%
“…Multiple cross-regulatory interactions were identified between the TOR and the Mitogen Activated Protein Kinase (MAPK) signalling pathways in the fission yeast and these cross-talk were proposed as mechanisms to elicit adaptive responses to extra- and intracellular conditions by regulating essential cellular functions [ 31 ]. MAPK signalling pathways, particularly those of mating and filamentous growth, were shown to be responsive specifically to intermediary levels of oxygen availability in the baker’s yeast.…”
Section: Introductionmentioning
confidence: 99%